Children with oral clefts are at greater risk for persistent low achievement in school than classmates. Issue 12 (7th September 2015) - Wehby, George L; Collett, Brent R; Barron, Sheila; Romitti, Paul; Ansley, Timothy
Abstract : Objectives: To examine trajectories in academic achievement for children with oral clefts versus unaffected classmates and explore predictors of persistently low achievement among children with oral clefts. Design: Longitudinal cohort study of academic achievement in a population-based sample. Setting and participants: Children born from 1983 through 2003 with oral clefts were identified from the Iowa Registry for Congenital and Inherited Disorders and matched to unaffected classmates by sex, school/school district and month and year of birth. Main outcome measures: Academic achievement was measured from Iowa Testing Programs data. Outcomes included achievement scores in reading, language and mathematics. Results: Academic achievement data were available for 586 children with oral clefts and 1873 unaffected classmates. Achievement trajectories were stable for both groups. Children with oral clefts were more likely than their classmates to be classified into persistent low achievement trajectories, including when adjusting for socioeconomic differences: OR=1.63, 95% CI 1.23 to 2.16 for reading; OR=1.73, 95% CI 1.29 to 2.31 for language; OR=1.45, 95% CI 1.05 to 1.99 for math. Predictors of low achievement were cleft palate only (vs other cleft types), adolescent mothers, low maternal education and less frequent use of prenatal care. Conclusions: Most children have steady academic trajectories and children with oral clefts are at greater risk for persistent low achievement in school than unaffected classmates. These findings support the need for routine, early screening for academic deficits in this population. Cleft palate only, low parental education and adolescent mothers are associated with increased risk for persistent low achievement.